Morphological characteristics and phylogenetic analyses reveal Scopuloides yunnanensis (Polyporales, Basidiomycota), a new wood-decaying fungus from China - Gu, Zirui; Zhou, Hongmin; Zhao, Changlin (Phytotaxa, 2024)
Wood-decaying fungi, as crucial decomposers in forest ecosystems, have been the subject of meticulous research. In this study, a new wood-decaying fungal species, Scopuloides yunnanensis, found in Yunnan, China, is proposed. Scopuloides yunnanensis was identified based on a comprehensive analysis of its membranaceous basidiomata, generative hyphae, lamprocystidia, projecting cystidia, and allantoid basidiospores. In addition to the morphology, phylogenetic analyses of ITS and nLSU rRNA markers were performed with Maximum Likelihood, Maximum Parsimony, and Bayesian inference methods, ensuring the robustness of our findings. The phylogenetic analysis showed that S. yunnanensis is sister to S. hydnoides. The new species’ description, illustrations, and results of the phylogenetic analysis are provided. In addition, an identification key to all Scopuloides species worldwide is provided.